Experimental poisoning by the fruits of Hovenia dulcis (Rhamnaceae) in cattle Intoxicação experimental pelos frutos de uva-Japão, Hovenia dulcis (Rhamnaceae), em bovinos - Cardoso T.C.* (2015)
Hovenia dulcis Thunberg (Japan grape) is a deciduous tree native of China and some parts of Japan. Over the last years, the tree has been used for shading in poultry farms of western and middle western Santa Catarina, spreading in the region. Cattle ingest the ripe fruits of H. dulcis fallen to the ground. The fruits were suspected to cause poisoning during fall and early winter, period of their maturation. The disease has been reproduced in 2004 by other authors with a single dose of 24.5g/kg. In the subsequent years no complaints regarding the toxicity of H. dulcis fruits have been reported, although many breeders observed that cattle continued to consume them during the ripening season. We administered the fruits at single doses of 30-50g/kg to nine calves; only two of them became seriously ill and one died. The clinical picture and lesions were similar to the poisoning reproduced in 2004; however, the dose required to reproduce the poisoning was 100% higher than the lethal dose found in 2004.